Managing reference rate risks in Islamic Financing through “Managed Tawarroq” - Al-Momani, Esraa (Jordan Journal of Islamic Studies, 2023)
This paper studied the usage of “Managed Tawaruq” as a tool for managing risks of margin changes in the Islamic Financing. The study has concluded that this tool cannot be considered as a Sharia Compliant tool for managing risks for a number of reasons, the most important ones are that goal of this tool is to directly link the price margin with the interest rates, and because it solely depends on intermediate transactions that are not intended for their own with no actual exchange of real goods.